Knowledge and Perception of Medical Negligence in Medical Students - Sapate A.B; Biradar V.R; Band R.M.; Petkar M.R.; Ghangale A.L (Indian Journal of Forensic Medicine and Pathology, 2025)
Introduction: Absence of reasonable care and skill, or willful negligence by medical practitioner in the treatment of a patient resulting in bodily/psychological injury or death of the patient is medical negligence. This survey was conducted to assess the knowledge and awareness of medical students and interns in a medical college. Materials & Methods: It is an observational cross-sectional study in which 306 IIIrd Professional M.B.B.S. Part-2 students & Interns participated in 10 multiplechoice questions based on different aspects of negligence in medical practice and its prevention. The data collected were tabulated and statistically analyzed to draw conclusions. Results: Out of 306 total respondents, 27.80% (n=85) had adequate knowledge, while 60.50% (n=185) had partial knowledge, and 11.80% (n=36) had poor knowledge. It was found that adequate knowledge was present in 36.41% (n=71) of IIIrd Professional M.B.B.S. Part-2 students, and 12.61% (n=14) of Interns. Conclusion: IIIrd Professional M.B.B.S. had better knowledge about medical negligence when compared to Interns showing labile memory of lessons taught in UG curriculum. A reasonable approach to tackle this issue could be to ensure better medico-legal training for medical students.